1991
DOI: 10.1002/art.1780340213
|View full text |Cite
|
Sign up to set email alerts
|

Tenidap, in contrast to several available nonsteroidal antiinflammatory drugs, potently inhibits the release of activated neutrophil collagenase

Abstract: Neutrophils contain a collagenase that is stored in a latent form within the specific granule. With cellular activation, the latent enzyme is activated in association with the production of a variety of oxidants, including hypochlorous acid. We evaluated 4 nonsteroidal antiinflammatory drugs (NSAIDs) currently on the market and the new antiinflammatory/antirheumatic drug tenidap for their effects on the release of activated collagenase. In contrast to the 4 NSAIDs, tenidap profoundly inhibited the release of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Such results are considered indicative of DMARD-like therapeutic effects [5][6][7][8]. Moreover, inhibitory effects on degranulation observed in preclinical in vitro [9] and in vivo [10] studies are observed ex vivo in human neutrophils following tenidap treatment of arthritic patients [11,12]. In a crossover study in man, tenidap, but not the reference cyclooxygenase inhibitor piroxicam, reduced levels of IL-6, indicating that cytokine reduction is independent of cyclooxygenase inhibition [13].…”
Section: Introductionmentioning
confidence: 87%
“…Such results are considered indicative of DMARD-like therapeutic effects [5][6][7][8]. Moreover, inhibitory effects on degranulation observed in preclinical in vitro [9] and in vivo [10] studies are observed ex vivo in human neutrophils following tenidap treatment of arthritic patients [11,12]. In a crossover study in man, tenidap, but not the reference cyclooxygenase inhibitor piroxicam, reduced levels of IL-6, indicating that cytokine reduction is independent of cyclooxygenase inhibition [13].…”
Section: Introductionmentioning
confidence: 87%
“…Tenidap sodium [(Z)-5-chloro-2,3 dihydro-3-(hydroxy-2-thienyl methy1ene)-Zoxo-1 H-indole-1-carboxamide, sodium salt] is a novel drug which has combined cyclooxygenase-and 5-lipoxygenaseinhibitory activity in vitro (15,16). Several of its properties, such as its ability to modulate cytokine synthesis (17), its in vitro activity in protecting cartilage integrity (18), its potent inhibitory action on the release of activated neutrophil collagenase (19), as well as its antiinflammatory and analgesic activities (20), make it an attractive antirheumatic drug. Recent findings also indicate that tenidap can reduce IL-1-stimulated MMP synthesis and expression by chondrocytes, by markedly reducing the level of IL-I receptor (21).…”
mentioning
confidence: 99%
“…In contrast to many anti-inflammatory agents which are carboxylic acids, the acidic nature of tenidap derives from its enolic character. This compound demonstrates biological and clinical properties which distinguish it from NSAIDs [10][11][12][13][14][15][16]. Here we report that tenidap inhibits 5-lipoxygenase metabolism of arachidonic acid in vitro, but that this activity could not be demonstrated in three animal models.…”
Section: Introductionmentioning
confidence: 66%